Development of Chlorpyrifos Sensor Using Molecularly Imprinted Polymer (MIP) Polyvinyl Alcohol (PVA)-Fe3O4 as Receptor - Afifah Muhimmatul Mustaghfiroh; Ani Mulyasuryani; Ulfa Andayani (Chemistry Department, The University of Brawijaya, 2019)
Development of a chemical sensor to detect chlorpyrifos has been carried out using a molecularly imprinted polymer (MIP) polyvinyl alcohol (PVA)-Fe3O4 as a membrane receptor. The MIP-Fe3O4 receptor is composed of polyvinyl alcohol (PVA) polymer, glutaraldehyde crosslinking reagent, citric acid catalyst, chlorpyrifos template, and Fe3O4. The MIP-Fe3O4 receptor is coated on the working surface of the screen-printed carbon electrode (SPCE) with a size of 1.5 x 3 mm2. In this study, the effect of adding concentrations of chlorpyrifos and citric acid into membrane receptor was studied. The chlorpyrifos concentrations applied were 0.05, 0.1, 0.5 and 1% (w/w) and the concentrations of citric acid were 9.2, 16.8 and 23.3% (w/w). Sensor performance is also influenced by pH and type of electrolyte. The best sensitivity of the sensor is produced in the concentration range of 10-13 - 10-6 M at 24 mV/decade with a response time of 150 seconds.